PENGARUH GOOD CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN - Friska Riftama Chaerudin; Sri Handayani (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This study aims to determine the effect of good corporate governance, intellectual capital and capital structure on financial performance in restaurant, hotel and tourism sub-sector companies for the period 2021-2023. This study is a quantitative study using a causal descriptive method. The sampling method used is the purposive sampling method with a population of 156 restaurant, hotel and tourism sub-sector companies. While the sample is 102 data. Secondary data was obtained through financial reports and annual reports available on the official website of the Indonesia Stock Exchange for the relevant period. Multiple regression analysis was used to analyze the data. The research findings show that: Intellectual capital has a positive effect on financial performance, GCG and capital structure do not affect financial performance. The results of this study provide a positive contribution to the company, where the success of a company is determined by the resources and capabilities it has so that it is able to convert these resources into economic benefits. This study also provides a theoretical contribution that is relevant to resource-based theory, where companies can achieve competitive advantage by relying on the resources they have.